Classification of underweight newborn by birth weight, gestational age and fetal growth, morbidity and mortality - Cabrera Candela, Walter (2015)
It has reviewed 4,668 births between 1970-1971. He found 295 live births of low weight, which constitute 6.32%. In 278 cases (94%) gestational age in completed weeks was determined. We have linked the birth weight with gestational age, having formed 7 groups of live births of low weight, establishing morbidity and mortality in each of these groups. Other classification, based on relating the above 7 groups with intrauterine growth curves, giving rise to 21 specific opportunities to study groups, having registered only 13 cases of these groups is made, establishing morbidity and mortality in each . The distribution of pathologies and the percentage of neonatal mortality are different in our groups to morbidity and mortality established in ratings given to newborns in general. The need for intrauterine growth curves for each socio-economic environment in particular, both for normal-weight newborns and for low birth weight poses.